Transformasi penerjemahan bentuk seksisme dalam novel Pasung Jiwa ke dalam novel Bound - Haque, Arina; Sajarwa, Sajarwa (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to seek the transformation that occurs in the translation of the sexism forms in the novel Pasung Jiwa, and its translation of the novel Bound. Research data was collected by observing and taking notes, which were then analyzed using the translational equivalence method and then described descriptively-qualitatively. The form of sexist speech is identified using the theory of Glick and Fiske. The meaning of the data obtained was searched using the KBBI VI monolingual dictionary and the Merriam-Webster dictionary. The types of transformation found in the translation is identified using the theory of Proshina, and the transformation will be analyzed lexically. The research results show that there are 48 forms of sexism by Glick and Fiske out of a total of three types of sexism, namely Hostile sexism, Benevolent sexism, and Ambivalent sexism. After identifying the forms of sexism that were found, the next transformation of lexical changes was that a total of 63 data were found with details of the data that appeared most frequently to those that appeared least, namely generalization, modulation, specification, compensation, metaphorical transformation, and finally differentiation.